The impact of organizational culture and human resource development practice on knowledge transfer performance through the mediation of knowledge assets - Muhammad Rusydi; Naidah Naidah; Arniati Arniati; Syarifuddin Sulaiman; Warda Warda (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The purpose of this research is to investigate the effect of organizational culture (OC) and human resource development practice (HR) on knowledge assets (KA) and knowledge transfer performance (KT). This type of research is survey research that takes samples from a population and uses a questionnaire as a primary data collection tool. The population in this study were all staff in the PT PLN (Persero) UIW Sulselrabar of 197 people. The sampling technique in this study used a saturated sample. The results of the study show that OC and HR have a significant impact on KA. KA has a significant impact on KT, while OC and HR are not significant on KT. Finally, the perceived benefits of OC and HR can create positive attitudes about KA.